The Relevance of Time Management in Academic Achievement: a Critical Review of the Literature - Ghafar, Zanyar Nathir (MultiTech Publisher, 2023)
Time is an integral aspect of existence. Time management is a crucial determinant that impacts all aspect of living. As human life progresses, both energy and physical strength tend to diminish. It is important to do several tasks within a certain time range. Any activity performed after the way of time becomes ineffective. It is essential to live in the present moment. The objective of this research paper is to have a thorough comprehension of the basic concepts of time management and its importance. To accomplish this goal, a thorough examination of the current review of literature was undertaken. The crucial element for effective time management has been shown to be work scheduling. The study highlights and investigates whether or not academic accomplishment is influenced by factors such as time management, learning motivation, and learning facilities.